Subsidising balkanisation: What China's 3G subsidies teach us about 5G Open RAN - Hosuk Lee-Makiyama (European Centre for International Political Economy (ECIPE), 2021)
Open RAN is increasingly becoming the answer to how to diversify 5G networks and beyond, especially in the light of a potential exclusion of China's participation in western networks. In recent times, the US and Japan have jointly pledged 4.5 billion to support its development. Much - or perhaps entirety - of this support is predesignated for the O-RAN Alliance, a closed-door and private industry consortium. State interventionism is back - in a sector hereto characterised by open western markets and free competition. The public support currently pledged to the O-RAN consortium bear many resemblances to the Chinese government's attempt to support TD-SCDMA, a unique standard for the Chinese market that was designed to support local vendors. Its use was a pre-condition for public subsidies for R&D or public procurement. As recent as 2020, the US Trade Representative reported on China's standard-setting practices and subsidies as one of the world's worst trade barriers. Those who advocate similar support in the West are either indifferent or nescient about how EU and US trade negotiators worked to address subsidies and opaque standard-setting. It is an open question whether the US and Japan will offer a level-playing field to European vendors - or non-O-RAN members who may develop their own Open RAN variants. Nowadays, Chinese scholars and senior officials openly talk of "TD-style innovation" as a disaster for the nation that delayed China's rollout of 4G and plunged the economy into a performance and innovation lag. A key lesson for policymakers today is how vendors that cannot survive without subsidies will not optimise the organisation for innovation but public grant-seeking. This is an eerie warning for the 5G debate in some western capitals.
Keywords: 330